Financial Feasibility of A Hair Care-Based Business: A Study Case of Sassle - Ramadhan, Aulia Fatah Harum; Irawan, Atika (Journal Integration of Social Studies and Business Development, 2024)
Hair loss, or alopecia, is a global concern, with 3.8% of Southeast Asia's population affected by Alopecia Areata, an autoimmune disorder. Traditional treatments like minoxidil and finasteride, while effective, often have side effects. To address this, Sassle, a haircare startup, developed an almond-based hair serum in collaboration with ITB's School of Pharmacy, offering a natural solution without adverse effects. Sassle has completed product development and is preparing to launch its go-to-market strategy. This study evaluates the financial feasibility of Sassle's product using primary data from Sassle's records and secondary data from industry comparables. Key financial metrics such as the Payback Period, Net Present Value (NPV), and Internal Rate of Return (IRR) were analyzed, along with a scenario analysis under pessimistic, base, and optimistic conditions. The base scenario indicated a payback period of 3 years and five months, a positive NPV of Rp381,007,156, and an IRR of 49%, surpassing the Weighted Average Cost of Capital (WACC) of 5.02%. In the pessimistic scenario, with a 25% sales reduction, the payback period was four years and 11 months, with a positive NPV of Rp265,828,152 and an IRR of 32%. With a 15% sales increase, the optimistic scenario predicted a 2-year, 1-month payback period, a positive NPV of Rp622,915,633, and an IRR of 67%. The findings confirm that Sassle's business model is financially viable and capable of substantial returns, providing critical insights for strategic decisions in investment, market expansion, and operational scaling.